Performance of Diesel Engine Operating with Waste Plastic Disposal Fuel - Mohd. Herzwan, Hamzah; Abdul Adam, Abdullah; Agung, Sudrajad; Nur Atiqah, Ramlan; Nur Fauziah, Jaharudin (scientific.net, 2013)
Nowadays, many researches are conducted to produce alternative fuel. In order to overcome increasing price of fossil fuel and environmental issues, fuel from natural sources such as palm, rapeseed and jathropa are increasingly being utilized to produce bio-fuel. Similar as natural source, waste product such as plastics and tires also can be processed to produce alternative fuel. In this paper, engine performance of diesel engine operating with 100% waste plastic disposal fuel (WPDF) is analyzed and compared to diesel fuel. The experiment is conducted using single cylinder YANMAR TF120M diesel engine which is operating at variable speed and constant load. The performance parameters that analyzed in the experiment are engine power, torque, combustion pressure and exhaust gas temperature. Results of the experiment shows that waste plastic disposal fuel (WPDF) potentially can be use as alternative fuel in diesel engine. However, based on the data obtained, performance of diesel engine operating with WPDF is lower compared to diesel fuel